Effect of Driver Distraction on Vehicle Speed Control. (September 2021) - Emily Parcell, M.S.; Shivani Patel, M.S.; Severin, Cameron; Cho, Yoona; Chaparro, Alex
Performing a secondary task while driving impairs various performance measures, including speed control. Distraction is associated with reductions in driving speed; however, this is often based on global measures of performance, such as course completion time or mean speed. This study investigated how a secondary task affected granular speed variation. Participants (N=16, ages 18-43) performed a secondary task of mentally subtracting pairs of numbers while negotiating a simulated road course. Various driving performance measures were obtained but only results for longitudinal velocity are reported. The results reveal that drivers exhibited significant increases and decreases (>2+/- SD) in vehicle speed under distraction, with participants showing a stronger tendency to decrease their speed (60% of the observed speed violations). This may explain why global measures of driving speed under distraction reveal a slowing down. These results may increase our understanding of the nuanced effects of distraction on driving and be useful for predicting/diagnosing distracted driving behavior.